Detoxification with titration and tapering in gamma-hydroxybutyrate (GHB) dependent patients: The Dutch GHB monitor project. (1st January 2017) - Dijkstra, Boukje A.G.; Kamal, Rama; van Noorden, Martijn S.; de Haan, Hein; Loonen, Anton J.M.; De Jong, Cor A.J.
Highlights: Gamma-hydroxybutyrate (GHB) detoxification with pharmaceutical GHB is a safe alternative to benzodiazepines. During detoxification anxiety decreased significantly but remains very high. Relapse rates of patients with GHB dependence after detoxification are high. Abstract: Background and aims: Gamma-hydroxybutyrate (GHB) detoxification procedures have been insufficiently studied for effectiveness and safety. Based on case reports, benzodiazepines are generally regarded as first-choice agents in GHB detoxification. Detoxification by titration and tapering (DeTiTap) with pharmaceutical GHB in an open-label consecutive case series of 23 GHB-dependent patients showed to be feasible, effective and safe. This study further explored the feasibility, effectiveness and safety of this detoxification procedure in a large group of patients. Method: A large observational multicenter study was carried out in six addiction treatment centers in the Netherlands. GHB-dependent inpatients (229 unique patients, 274 admissions) were titrated on and tapered off with pharmaceutical GHB. Results: Successful detoxification was achieved in 85% of cases. Detoxification was carried out in 12.5 days in most patients. The DeTiTap procedure proved to be feasible and significantly reduced the experienced withdrawal symptoms and craving (p ≤ 0.001). Several symptoms were found to influence the course of subjective withdrawal symptoms. During detoxification, psychological symptoms such as depression, anxiety, and stress decreased (p ≤ 0.05). The main complications were hypertension and anxiety. Six patients were sent to the general hospital for observation, but all six were able to continue detoxification in the addiction treatment centers. Most patients (69%) relapsed within three months after detoxification. Conclusions: The DeTiTap procedure using pharmaceutical GHB seems a safe alternative to benzodiazepines as a GHB detoxification procedure. However, the high relapse rates warrant further investigation.